Ultraviolet-assisted Fenton digestion of peach juice for the determination of nickel by flame atomic absorption spectrometry (FAAS) - Ayyildiz, Merve Firat; Saylan, Meltem; Yazici, Elif; Chormey, Dotse Selali; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2024)
This study describes a simple and efficient UV-Fenton digestion of peach juice for nickel determination by flame atomic absorption spectrometry (FAAS). Herein, a hybrid of magnetic nanoparticles (MNPs) and hydrogen peroxide were used to digest the peach juice with UV irradiation. The effects of experimental parameters were systematically optimized to obtain the best digestion conditions. A laboratory-scale closed-box isolated reactor setup was designed for the digestion experiments in this study. A low relative standard deviation of 6.8% for the lowest calibration standard established the digestion method's good precision for replicate samples. Several peach juice samples were utilized in spike recovery experiments to validate the method's applicability and accuracy. The recoveries calculated for the samples spiked at four concentrations were satisfactory (92-106%), indicating that this simple and effective analytical approach can be utilized as an alternative to conventional microwave digestion.
Keywords: Flame atomic absorption spectrometry (FAAS); magnetic nanoparticles; nickel; UV-Fenton digestion; LIQUID-LIQUID MICROEXTRACTION; WASTE-WATER; UV-FENTON; OXIDATION; COBALT; IRON; PRECONCENTRATION; OPTIMIZATION; DEGRADATION; EXTRACTION; Chemistry